Conjugate natural convection in an inclined square porous enclosure with finite wall thickness and partially heated from its left sidewall - Ahmed, S.E.; Hussein, A.K.; El-Aziz, M.M.A.; Sivasankaran, S. (Begell House, 2016)
The analysis of conjugate natural convection heat transfer in a square inclined enclosure filled with a porous medium and adjacent to the walls of finite thickness is investigated numerically using the finite volume method. While a uniform heat source is located on a part of the left inclined sidewall of the enclosure, the right inclined sidewall is maintained at a constant low temperature. The top and bottom walls are assumed adiabatic together with the remaining parts of the left inclined sidewall. Numerical computations are performed in wide ranges of the thermal conductivity ratio, enclosure inclination angle, dimensionless wall thickness, and dimensionless heat source length. The results are presented to give a parametric study showing the influence of these parameters on the flow and the heat transfer characteristics inside the enclosure. The results of the present work explain that the local Nusselt number of fluid phase increases when the thermal conductivity ratio increases, while the local Nusselt number along the heat source decreases as the thermal conductivity ratio increases. On the other hand, the average Nusselt number at the solid walls and fluids increases when the inclination angle increases from φ = 0o to φ = 45o, decreases slightly at φ = 60o, and decreases significantly when φ = 90o. Moreover, the fluid circulation intensity within the porous medium can be improved when considering a small wall thickness, high thermal conductivity ratio and when the heat source length increases. The results are compared with other published results and they found to be in good agreement.